The spatial and dynamic impact of air pollution on public health: Evidence from China 2000–2021 - YuMing Qin; XueQin Lin; Ye Duan (PLoS ONE, 2025)
China’s rapid economic growth and improving quality of life have led to severe air pollution, primarily due to the country’s development model. This pollution not only raises public health risks but also shortens life expectancy, drawing significant attention from both the public and the government. This study focuses on 31 provincial-level regions within China, utilizing data collected annually from 2000 to 2021. It begins by examining the spatial relationships between air pollution and public health, then delves into how air pollution and various influencing factors affect public health outcomes. Lastly, the research investigates how these effects vary across different regional contexts. The findings show a clear connection between the medical visits for diagnosis and treatment and the levels of air pollution across different provinces. The spatial econometric model reveals that PM2.5 levels, industrial SO2 emissions, and smoke and dust emissions from industries all significantly increase medical visits for diagnosis and treatment. A 1% rise in PM2.5, SO2, or industrial smoke and dust emissions leads to increases of 0.2884%, 0.0563%, and 0.1365%, respectively, in medical visits. This suggests that air pollution contributes to a decline in public health. The impact of air pollution on public health shows considerable variation across different regions, including the eastern, central, and western parts of the country. The results of this study offer fresh insights into how air pollution affects public health, providing important guidance for policies aimed at improving air quality and protecting the health of citizens.